Exploring the evolution of giant molecular clouds in one of the nearest spiral galaxies M33 - Konishi, Ayu; Muraoka, Kazuyuki; Tokuda, Kazuki; Fujita, Shinji; Yamada, Rin I.; Demachi, Fumika; Tachihara, Kengo; Fukui, Yasuo; Kobayashi, Masato I.N.; Tsuge, Kisetsu; Kawamura, Akiko; Onishi, Toshikazu (Resolving the Rise and Fall of Star Formation in Galaxies, 2021)
The evolution of giant molecular clouds (GMCs), which are the main sites of star formation, is essential for unraveling how stars form and how galaxies evolve. We analyzed the M33 CO(J = 2–1) data with spatial resolution of 39 pc obtained by ALMA-ACA 7 m array combined with IRAM 30 m. We identified 736 GMCs and classified them into three types; Type I: associated with no H ii regions, Type II: associated with H ii regions with the Hα luminosity L(Hα) < 1037.5erg s−1, Type III: associated with H ii regions with L(Hα) > 1037.5erg s−1. We found that mass, size, and velocity dispersion of GMCs slightly increase in the order of Type I, II, and III GMCs. Type III GMCs mainly exist in the spiral arm, while many of Type I and Type II GMCs are distributed in the inter-arm. Assuming that the star formation proceeds steadily, we roughly estimated the total GMC lifetime of 30 Myr.
CRIS-Team Scopus Importer:2024-12-16
Keywords: galaxies: Local Group; galaxies: spiral; ISM: molecules; stars: formation